On the evolution of the concept of two light reactions and two photosystems for oxygenic photosynthesis: A personal perspective - G. GOVINDJEE (Photosynthetica, 2023)
I present here a personal perspective of the evolution of the two-light reaction two-pigment scheme for the electron transport in oxygenic photosynthesis - as I have lived through it - first as a graduate student of Robert Emerson, from September 1956-January 1959, and then of Eugene Rabinowitch from February 1959-September 1960. I have provided here some of the key published work in my way and have also provided a few photographs. It is essential to remind ourselves upfront that different individuals may have different recollections of the same event (see e.g., the Japanese movie 'Rashomon' https://en.wikipedia.org/wiki/Rashomon). Thus, I encourage others to write about their perspective. Further, I recognize, upfront, the support and encouragement I have received from Robert Blankenship for writing this perspective, and from Győző Garab for submission of this story to Photosynthetica. I begin my perspective with a dedication to Robert Emerson, whose pioneering work led to the concept of the two-light reaction two-pigment system in oxygenic photosynthesis.